Pengaruh Ukuran Perusahaan, Leverage, Pertumbuhan Penjualan,Profitabilitas dan Kebijakan Dividen terhadap Harga Saham - Apri, Syahli; Anugerah, Rita; Humairoh, Fitri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This research aims to test and prove empirically the influence of company size, leverage, sales growth, profitability and dividend yield on stock prices. The population of this research is LQ45 index companies registered at BEI for the period 2018-2022 with a total sample of 100. The sampling technique uses purposive sampling. The data analysis method used in this research is a quantitative analysis technique with a multiple regression hypothesis testing formula processed with the help of the Statistical Product and Service Solution (SPSS) data processing software program version 25.0 for windows. The results of hypothesis testing show that the variables of company size, leverage, and profitability have a significant effect on stock prices, while sales growth and dividend yield are not proven to be influential.